Predicting Counselling Service Utilization Patterns with the MMPI-2 College Maladjustment Scale - Stewart, Donald W. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study reports on the initial results of a predictive validity study of the College Maladjustment (Mt) Scale from the recently revised Minnesota Multiphasic Personality Inventory. Firsttime personal counselling clients at a Canadian university completed the Mt scale at intake and were tracked administratively through a departmental client database. From this database, information regarding their service utilization patterns during the academic year (September to April) was collected. The results indicated that Mt scale scores were significantly associated with total number of client contacts, number of scheduled appointments, frequency of contacts, and number of cancellations. Implications for the predictive validity of the scale and its utility as an aid to service delivery and planning are discussed.